Comparative Analysis of the Financial Performance of BPRS Adeco and BPRS Serambi Mekkah in Langsa City (2019–2024) - Zefri Maulana; Alfian; Muhammad Ikhwan bin Mauluddin; Nadiya Ulfa (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: This study compares the financial performance of BPRS Adeco and BPRS Serambi Mekkah during 2019–2024 using ROA, BOPO, NPF, and FDR indicators. The study is important to evaluate the effectiveness and financial health of Islamic rural banks. Research Methods: This research uses a quantitative descriptive comparative approach. Secondary data were collected from the financial reports of both banks and analyzed using financial ratio analysis and the Mann-Whitney U Test with SPSS version 25. Results: The results show significant differences in ROA, BOPO, and FDR (p < 0.05), where BPRS Adeco demonstrates better profitability, operational efficiency, and liquidity management than BPRS Serambi Mekkah. However, there is no significant difference in NPF performance (p > 0.05), indicating similar financing quality between the two banks. Conclusion: BPRS Adeco has better financial performance compared to BPRS Serambi Mekkah. The findings highlight the importance of efficient operations and balanced liquidity management in maintaining the sustainability of Islamic rural banks.